Menguji Konflik Peraturan Perundang-undangan Pusat dan Daerah - Samsul Wahidin (Jurnal Hukum IUS QUIA IUSTUM, 2003)
Basically, only one legal system that served national interests. Yet, at this moment between Central Goverment and Local Government has tendency to dichotomize administration law. Harmonization perspective of legal product between Central and Local Governmentshould be focused as interreleted components besides that the law enforcement should be implementated in good manner.